2017
DOI: 10.1017/s0007114517001350
|View full text |Cite
|
Sign up to set email alerts
|

Dietary magnesium intake and fracture risk: data from a large prospective study

Abstract: Research considering the relationship between dietary magnesium (Mg) and osteoporosis and fractures are sparse and conflicting. We therefore aimed to investigate Mg intake and the onset of fractures in a large cohort of American men and women involved in the Osteoarthritis Initiative (OAI) over a follow-up period of 8 years. Dietary Mg intake (including those derived from supplementation) was evaluated through a food frequency questionnaire at baseline and categorized using gender-specific quintiles; osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Furthermore, magnesium supplements have been shown to improve BMD in osteoporotic women [ 98 , 99 ] and in young people [ 100 102 ]. Moreover, high dietary magnesium intake reduced prospectively the risk of osteoporotic fractures in middle-aged men and women [ 103 ]. The relationship between magnesium and bone health can be explained by different mechanisms.…”
Section: Hypomagnesemia and Endocrine Diseasesmentioning
confidence: 99%
“…Furthermore, magnesium supplements have been shown to improve BMD in osteoporotic women [ 98 , 99 ] and in young people [ 100 102 ]. Moreover, high dietary magnesium intake reduced prospectively the risk of osteoporotic fractures in middle-aged men and women [ 103 ]. The relationship between magnesium and bone health can be explained by different mechanisms.…”
Section: Hypomagnesemia and Endocrine Diseasesmentioning
confidence: 99%
“…No randomized studies evaluating the effect of magnesium on bone disease are available, but small-size studies have associated low serum magnesium levels with osteoporosis [35,36]. In older subjects, a low intake of magnesium causes excessive calcium release from the bone, which further worsens bone fragility and increases the risks of fractures and falls [37]. A cross-sectional analysis of a cohort of subjects in the UK evaluating the influence of dietary magnesium and potassium intakes on bone density and fracture risk found a lower hip fracture risk in both men and women with a higher intake of these minerals, but these results did not hold after adjustment for multiple testing [38].…”
Section: Other Mineralsmentioning
confidence: 99%
“…Thus, in this study, we prescribed ALF instead of Denotas ® Chewable supplementation; however, it is recommended to use Denotas ® Chewable instead of active vitamin D supplementation since Denotas ® Chewable also includes Mg, and denosumab might have decreased the serum Mg level when denosumab is used for a long time. In addition, Veronese et al have very recently reported that dietary Mg intake has a protective effect for and lower risk of future osteoporotic fractures [ 32 ]. Collectively, a prospective study will be required to see whether or not Mg supplementation affects bone metabolism and fracture occurrence in a large cohort study.…”
Section: Discussionmentioning
confidence: 99%